Application of Immanuel Kant's Retributive Theory in Death Penalty Sentencing for Premeditated Murder Following Constitutional Court Decision No. 21/PUU-VI/2008 - Sujono, Imam (PT. Riset Press International, 2025)
This study examines the application of Immanuel Kant's retributive justice theory in judicial decisions imposing death sentences for premeditated murder cases in Indonesia, particularly following the landmark Constitutional Court Decision No. 21/PUU-VI/2008. The research employs a normative juridical approach, analyzing secondary legal materials including legislation, court decisions, legal doctrines, and philosophical theories. Kant's retributive theory posits that punishment must be proportionate to the moral culpability of the offender, embodying the principle of ius talionis. However, the Constitutional Court's decision has reframed the death penalty as an exceptional and alternative sanction, requiring judges to consider principles of proportionality and individualization. This study reveals a fundamental tension between classical Kantian retributivism, which demands absolute proportionality regardless of consequentialist considerations, and the Constitutional Court's approach that increasingly emphasizes human rights protection and gradual abolitionism. The findings demonstrate that while judges rhetorically invoke retributive principles in their reasoning, practical application has become constrained by constitutional imperatives that prioritize rehabilitation and the right to life. This normative contradiction suggests an evolutionary shift in Indonesia's criminal justice philosophy from pure retribution toward a more nuanced balancing of retributive, rehabilitative, and human rights considerations.